Temporal Coordination in Mother–Infant Vocal Interaction: A Cross-Cultural Comparison - Farran, Lama K.; Yoo, Hyunjoo; Lee, Chia-Cheng; Bowman, Dale D.; Oller, D. Kimbrough (Frontiers in Psychology, 2019)
Temporal coordination of vocal exchanges between mothers and their infants emerges from a developmental process that relies on the ability of communication partners to co-coordinate and predict each other's turns. Consequently, the partners engage in communicative niche construction that forms a foundation for language in human infancy. While robust universals in vocal turn-taking have been found (Stivers et al., 2009), differences in the timing of maternal and infant vocalizations have also been reported across cultures. In this study, we examine the temporal structure of vocal interactions in 38 mother-infant dyads in the first two years across two cultures—American and Lebanese—by studying observed and randomized distributions of vocalizations, focusing on both gaps and overlaps in naturalistic 10-minute vocal interactions. We conducted a series of simulations using Kolmogorov-Smirnov (K-S) tests to examine whether the observed responsivity patterns differed from randomly generated simulations of responsivity patterns in both Arabic and English for mothers responding to infants and for infants responding to mothers. Results revealed that both mothers and infants engaged in conversational alternation, with mothers acting similarly across cultures. By contrast, significant differences were observed in the timing of infant responses to maternal utterances, with the Lebanese infants' tendency to cluster their responses in the first half second after the offset of the Lebanese mothers' utterances to a greater extent than their American counterparts. We speculate that the results may be due to potential phonotactic differences between Arabic and English and/or to differing child-rearing practices across Lebanese and American cultures. The findings may have implications for early identification of developmental disorders such as autism spectrum disorders within and across cultures.